2012
DOI: 10.1097/ypg.0b013e32834915ae
|View full text |Cite
|
Sign up to set email alerts
|

Association of HLA-DRB1 alleles and neuropsychological function in autism

Abstract: Evidence suggests an association between autism and immune dysfunction. The associations between human lymphocyte antigen (HLA)-A2, B44, DRβ1*04 (DR4), C4B, and haplotype B44-SC30-DR4 and autism have been reported in western countries but there is a lack of such information in Asian population. This study aimed to assess the association between HLA-DRB1 allele frequencies and the clinical phenomenology of autism. The sample included 141 participants (male, 87.2%), who were diagnosed with autistic disorder base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 21 publications
0
29
0
2
Order By: Relevance
“…In addition, patients with autism and DR4, DR11, or DR14 had different performance on intelligence and neuropsychology tests. Despite a relatively small sample size and a case-control association design, the fi ndings suggest HLA-DRB1 gene might be associated with autism in Han Chinese (31).…”
Section: Discussionmentioning
confidence: 80%
“…In addition, patients with autism and DR4, DR11, or DR14 had different performance on intelligence and neuropsychology tests. Despite a relatively small sample size and a case-control association design, the fi ndings suggest HLA-DRB1 gene might be associated with autism in Han Chinese (31).…”
Section: Discussionmentioning
confidence: 80%
“…Among the top-ranking genes were members of the HLA family ( HLA-A , HLA-DPA1 , and MICC ) as well as genes encoding for proteins involved in acetylcholine transport and synthesis ( SLC18A3 and CHAT ). A growing number of studies suggest a role for the HLA family of genes in different psychiatric disorders such as schizophrenia, autism, and depression (Chien et al , 2012; Sullivan et al , 2012; Al-Hakbany et al , 2014; Kodavali et al , 2014; Morgan et al , 2016). However, although this report recalls the potential involvement of the HLA family in ADHD, conflicting results exist regarding this matter (Odell et al , 1997; Payton et al , 2003; Aureli et al , 2008).…”
Section: Discussionmentioning
confidence: 99%
“…From the same study, an increased disease risk was found among families with history of autoimmune disease [31]. Furthermore, a study from china found that DR4, DR11, and DR14 had a different effect on intelligence and neuropsychology tests among autistic children [32], unlike an earlier study, which shows no significant association between autism and HLA [33]. …”
Section: Discussionmentioning
confidence: 99%